Vandalisme Dalam Kegiatan Wisata Hutan Di Taman Kupu-Kupu Gita Persada Bandar Lampung - Anggih Pararinarno; Agus Setiawan; Jani Master (Jurnal Sylva Lestari, 2015)
The Gita Persada Butterfly Park is one of the examples of a region that can be selected as an object of forest tourism which is located near city areas. This kind of tourism has own interest, so make enthusiasts of the travellers to visit this forest tourism. The travellers who visiting this park were assumed would create the negative impacts such as vandalism. The goals of this research are to identify the forms of the tree's vandalism and the group of ages from the travellers who did the vandalism, and than knowing the perceptions of the travellers against the vandalism. This research was done in January-February 2015 by using an observation method and interview. The plant's percentage that suffered vandalism at the location that used as a tourism activity is 8.91%. The plant's percentage that suffered vandalism at the location that not used as a tourism activity is 10.91%. Generally, the visitors have perceptions these vandalism activities damage trees and the beauty of the tourism object as well as they are needed the prevention acts by the orginizer of Gita Persada Butterfly Park about vandalism activities. Keywords: forest tourism, vandalism, gita persada butterfly park